Vitamin D deficiency, supplementation, and colorectal cancer outcomes: interactions with obesity and risk profiles - Naji, Basmalah; Eltawil, Menatalla; Nemer, Najla; Abdelazim, Omer; Patil, Jayaditya D.; Fredericks, Salim (Frontiers in Medicine, 2025)
BackgroundVitamin D deficiency, colorectal cancer, and tumor progression are increasingly linked in recent research. Beyond its well-established roles in bone metabolism and immune regulation, vitamin D has emerged as a potential modulator of cancer prevention and prognosis, particularly in colorectal cancer, where deficiency may worsen outcomes.PurposeVitamin D is critical in the prevention and prognosis of colorectal cancer, such as colorectal adenocarcinoma. This review aims to explore the impact of Vitamin D deficiency on colorectal cancer progression and assess the role of vitamin D supplementation in improving outcomes.MethodsA narrative review was conducted, utilizing five databases: PubMed, Medline Plus, ScienceDirect, Scopus, and Google Scholar, focusing on human studies published in the last 15 years (from 2012 to 2025). Priority was given to primary studies like randomized controlled trials and cohort studies, while systematic reviews were included for broader context. Exclusion criteria included animal studies, non-English papers, and non-peer-reviewed content.ResultsThe review synthesizes evidence from 33 primary studies and 16 high-quality reviews. Findings indicate that vitamin D supplementation may enhance prognosis by influencing serum levels, immune modulation, and gut microbiota. However, clinical trials results are mixed, particularly concerning optimal dosing, genetic variability, and factors like obesity.DiscussionVitamin D supplementation shows promise in improving colorectal cancer prognosis, but further research is necessary to refine dosing strategies and develop personalized therapies tailored to individual patient needs.